Adoption of farm mechanization for clean air: Evidence from farm trials in Pakistan - Ashok K. Mishra; Jaweriah Hazrana; Takashi Yamano; Noriko Sato; Babur Wasim Arif (Asian Development Bank (ADB), 2024)
Many rice farmers burn stubble and straw after harvest, which worsens air pollution. This paper examines the impact of training on the adoption of advanced rice harvesting technologies that reduce the need for crop burning. It uses data from a cluster randomized controlled trial in Pakistan. The results reveal that the training program improved the farm performance of rice growers. The cost-benefit analysis shows that farmers who received the training and used improved mechanical rice harvesting generated higher profits, an average gain of PRs19,784 per acre. The results highlight the potential of targeted extension strategies to accelerate the adoption of productivity-enhancing and sustainable technologies among smallholder farmers.
Keywords: C31; O33; Q12; Q16; 330; rice farming randomized control trial; difference-in-difference method; revenues; harvest losses